2020
DOI: 10.1177/0961203320904155
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity and damage in hospitalized lupus patients: a Sabah perspective

Abstract: Objective Systemic lupus erythematosus (SLE) is a complex multi-systemic autoimmune disease with variable levels of activity that may wax and wane within the same patient over the years. In view of the scarcity of data about lupus in the East Malaysian population, we aimed to study the disease activity and damage index in patients with SLE hospitalized in a tertiary center in Sabah, East Malaysia. Methods We retrospectively studied all patients with SLE admitted from 1 January 2013 to 31 December 2015. Demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
6
12
0
Order By: Relevance
“…This is a survival study of an inception cohort of SLE patients diagnosed since 1995. Our results showed that the overall 10-year survival of our SLE patients was 92.9%, which is similar to those reported in Asian studies after the 2000s ( 9 11 , 16 , 18 , 21 , 24 ). However, direct comparison is not feasible because the cumulative survival rate computed by the Kaplan–Meier method was not reported in most of these studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is a survival study of an inception cohort of SLE patients diagnosed since 1995. Our results showed that the overall 10-year survival of our SLE patients was 92.9%, which is similar to those reported in Asian studies after the 2000s ( 9 11 , 16 , 18 , 21 , 24 ). However, direct comparison is not feasible because the cumulative survival rate computed by the Kaplan–Meier method was not reported in most of these studies.…”
Section: Discussionsupporting
confidence: 90%
“…Although there have been a number of survival studies of SLE in the past decade, not too many were performed in the Asian populations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Analysis of the survival of hospitalized patients (9,22), those admitted to the intensive care unit (12,19) or referred to tertiary centers (23), subsets of patients with nephritis (14), neuropsychiatric manifestations (17), or pulmonary hypertension (15) in some studies would create bias in the mortality rate. Moreover, the follow-up of most of these Asian studies was not long enough to look at the trend of survival over time.…”
Section: Introductionmentioning
confidence: 99%
“…However, mortality rates and specific causes of death have varied throughout the last decades [4,[13][14][15][16]. Other groups have previously analyzed the causes of admission in SLE patients worldwide, with different results limited in many cases by sample size, monocentric design, and short follow-up periods [17][18][19][20][21][22][23][24][25]. Our study analyzes data from 99.859 admissions of SLE patients between 1997 and 2015, thus offering quite a wide view of the whole picture in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…According to our analysis, hospital admissions and deaths due to active SLE decreased dramatically from the late 1990's to the 2010-2015 period. Several studies have identified SLE itself as the main cause of hospital admission, with a wide range between 8.1 and 86.3% [17][18][19][20][21][22][23][24][25][26]. On the other hand, other studies have shown a significant downward trend in SLE-related admissions [19,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation